The importance of public relations skills for art students in the age of cultural industries development - Hoàng, Hòa Bình (2020)
Many cultural forums around the world are still debating about the existence of cultueral inclustries. Some opinions say that art is made up of the innate talents talents of the artists, the indestrialization of culture may lose, its inherent meaning. Some opposite opinions say that the cultural industries have no difference from other industries and these industries of creatives need serious attention and policy, just like nay other business. However, it is undeniable that there has been an existence of the cultual indeustries, although it is in a very earlier stage than that of other industries. The decisive elements to the development are the students studying art